A Determination of toxic heavy metals content in some cosmetic products commonly used among high school students - Trang, Hà Thuỳ; Luyện, Nguyễn Đình; Khánh, Lê Ánh; Kiên, Trương Trung (Hue University Journal of Science: Natural Science, 2021)
Content of some toxic metals (Pb, Cd, and As) in 18 cosmetic samples that high-school students in cities, plains, and mountainous regions often use is examined and determined by using atomic absorption spectroscopy with high reliability and accuracy. Their content is assessed according to the cosmetic type and compared with Vietnam and ASEAN’s standards. It is also compared with that in authentic cosmetics, determined by the same method.